Do anions influence the polarity of protic ionic liquids? - Shukla, Shashi Kant; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2012)
Polarity studies in two classes of imidazolium-based protic ionic liquids (PILs) possessing [HSO4](-), [HCOO](-),[CH3COO](-) and [CH3CH2COO](-) anions were carried out using a solvatochromic method from 298.15 to 353.15 K. For 1-methylimidazolium class of PILs, ET(30) was found to be independent over the entire range of temperature, while ET(30) was noted to decrease with a rise in temperature in the case of 1-butylimidazolium class of PILs containing [CH3COO](-) and [CH3CH2COO](-) anions. The ET(30) value decreases in both the classes upon varying the anions ([HSO4](-), [HCOO](-), [CH3COO](-) and [CH3CH2COO](-)). The E-T(30) value is controlled by hydrogen bond acceptor basicity, b, and dipolarity/polarizability, pi*. The E-T(30) value for PILs varies inversely to the strength of the coulombic interaction between ions in PILs. Strong interactions between ions lead to lower E-T(30) values. Unlike the poor thermal effect on E-T(30), the Kamlet-Taft parameters i.e. alpha, beta and pi* have pronounced thermal effect in the imidazolium-based PILs. Variation in the Kamlet-Taft parameters is controlled by the stabilization of ions and the degree of proton transfer from Bronsted acid to Bronsted base.